THE USE OF EGRA TECHNIQUE IN TEACHING WRITING NARRATIVE TEXT - Rayu, Rayu; Regina, Regina; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to find out the effectiveness of teaching writing narrative text using EGRA technique. To achieve the objectives of the research, a pre experimental study was conducted. This research was conducted at SMA St. Fransiskus Asisi Pontianak with the sample of the research was the eleventh grade of science students in academic year 2017/2018 which was chosen by using cluster random sampling technique. The findings of the research obviously showed that there was a significant difference of the students’ achievement before and after EGRA technique was applied, and that the use of the technique had a highly significant effect on the students’ writing shown by the students’ improved scores. To sum up, the present research findings proved that the use of EGRA technique is highly effective in teaching writing to the eleventh grade of science students of SMA St. Fransiskus Asisi Pontianak in academic year 2017/2018. Keywords: EGRA Technique, Teaching Writing, Writing Narrative Text.